The provincial deputation in Mexico : harbinger of provincial autonomy, independence, and federalism - Benson, Nettie Lee (Special publication of the Institute of Latin American Studies, the University of Texas at Austin., 1992)
Mexico and the United States each has a constitution and a federal system of government. This fact has led many historians to assume that the Mexican system of government, established in the 1820s, is an imitation of the U.S. model. But it is not. In this new interpretation of the independence movement, Nettie Lee Benson tells the true story of Mexico's transition from colonial status to a federal state. She traces the Mexican government's beginning to events in Spain in 1808-1810, when provincial juntas, or deputations, were established to oppose Napoleon's French rule and govern the country during the Spanish monarch's imprisonment. These provincial deputations proved so popular that ultimately they became the established form of government throughout the provinces of Spain and its New World dominions. It was the provincial deputation, not the United States federal system, that provided the model for the state legislative bodies that were eventually formed after Mexico won its independence from Spain in 1821. This finding - the result of years of painstaking archival research - strongly confirms the independence of Mexico's political development from U.S. influence. Its importance to a study of Mexican history cannot be overstated.